2015
DOI: 10.1080/00981389.2014.964447
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence Skills Training for African-American Breast Cancer Survivors: The Effects on Health Literacy, Medication Adherence, and Self-Efficacy

Abstract: There are gaps in research regarding medication adherence, self-efficacy in proper medication adherence, and health literacy among breast cancer survivors. This pilot randomized controlled study was conducted to provide information addressing health literacy with respect to medication adherence and self-efficacy in African American breast cancer survivors. The study sample consisted of an intervention group (n = 24) of medication adherence skills training (MST) and a control group (n = 24), with a total sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…). Of the 44 full‐text articles reviewed, 17 met the inclusion criteria by addressing the relation of HL with various self‐management behaviors in cancer (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). Of the 44 full‐text articles reviewed, 17 met the inclusion criteria by addressing the relation of HL with various self‐management behaviors in cancer (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight different measures of HL were used: the Rapid Estimate of Adult Literacy in Medicine (REALM; 7 studies); the Test of Functional Health Literacy in Adults–United Kingdom (UK‐TOFHLA; 1 study); the Short Test of Functional Health Literacy in Adults (S‐TOFHLA; 5 studies); the Short Assessment of Health Literacy in Spanish Adults (2 studies); the Measurement of Health Literacy in Europe–German Short Form (1 study); the Functional Communicative and Critical Health Literacy Scale–Dutch (1 study); and the Brief Health Literacy Screen (1 study) . Two studies used more than 1 measure of HL, and 1 study created a hybrid measure from REALM and S‐TOFHLA . Most studies, such as REALM and the Test of Functional Health Literacy in Adults (TOFHLA), included HL measures that primarily focus on the functional definition of HL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Husson et al8 explored the relationship between HL and health-related quality of life and found that low subjective functional HL among colorectal cancer survivors was associated with lower levels of physical activity and poorer health-related quality of life. Rust et al9 studied the relationship between initial HL and medication adherence, as well as initial HL and self-efficacy, and the results indicated that individuals with higher HL were more likely to have higher levels of self-efficacy and were more likely to adhere to medication instructions. Jin et al10 conducted a cross-sectional survey to examine the functional HL among older adults and identify influencing factors that can predict medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Social skills training is an intervention that utilizes learning activities and other behavioral techniques to enable patients with schizophrenia to acquire disease management and independent living skills to improve their functioning in their communities [10]. Reviews of trials [11,12,13,14,15] such as a specialized assertive intervention program (OPUS) concluded that social skills training had a positive effect on medication adherence and decreased rehospitalization rates. However, the impact of social skills training on patients' symptoms, aggressive behaviors, and quality of life was moderate [13].…”
Section: Introductionmentioning
confidence: 99%